2017
DOI: 10.1016/j.juro.2016.11.104
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of the Proportion of Ductal Component in Ductal Adenocarcinoma of the Prostate

Abstract: The prognosis for ductal adenocarcinoma can be stratified by the proportion of the ductal component. This marker could potentially be used as a surrogate for poor prognosis or as a determinant for adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…In general, DA is recognized as an adverse prognostic factor. 4,5,[10][11][12][13][14][15][16] In the present study, the prognostic Cases with IDC-P vs cases with pure AC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, DA is recognized as an adverse prognostic factor. 4,5,[10][11][12][13][14][15][16] In the present study, the prognostic Cases with IDC-P vs cases with pure AC.…”
Section: Discussionmentioning
confidence: 99%
“…3 Usually, DA presents in two forms: pure DA and DA mixed with acinar adenocarcinoma of the prostate (AC). 4,5 It was reported that mixed DA accounts for 3.0 to 12.7% of all PCa patients, while pure DA accounts for less than 1.0% of all PCa patients. 6 Although still controversial, 7 the presence of DA in either radical prostatectomy (RP) specimens or prostate biopsy (PBx) specimens is generally known as an adverse prognostic factor in patients with nonmetastatic PCa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the study by Jang et al. suggested this relationship, it did not distinguish ductal percentage as an independent risk factor for recurrence from the greater tumour volume typically observed in ductal tumours. Our present study supports the growing consensus that high ductal proportion heralds poor prognosis, but further establishes that this occurs regardless of PTI (as a surrogate of tumour volume, controlling for prostate size).…”
mentioning
confidence: 91%
“…While high ductal proportions have been presumed to be associated with poor prognosis, the literature supporting this conclusion is inconsistent, suggesting either no relationship or, in a single study, an increased risk of BCR with high ductal proportion . While the study by Jang et al.…”
mentioning
confidence: 97%